Visual Merchandising and Store Design in Rural Retail Outlets - Bonga, Gagandeep; Kumar , Babita; Rajini, (Gyan Management Journal, 2011)
India, retailing is still in its evolvingstage and the sector is witnessing a series of experiments across :
Keywords: Visual Merchandising; Store Design; DCM; Primary data